Objets inscrits du Fayoum: Compléments d'enquête - Bénazeth, Dominique (Journal of Coptic studies, 2025)
The update published here refers to an article by the same authors published in a recent issue of the Journal of Coptic Studies (2023), which listed "false" inscriptions on wooden and metal objects. It reports on the identification of new objects and explains the techniques used.